2015
DOI: 10.1016/j.anr.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of School Nurses' Self Efficacy between Multicultural Attitude and Cultural Sensitivity in Korean Elementary Schools

Abstract: Given the meaningful influence of positive multicultural attitude on cultural sensitivity and significant mediator effect of self efficacy as a school nurse between the two variables, the strategies to cultivate a positive multicultural attitude and enhance school nurses' self efficacy in their unique role should be considered in a training program. School nurses' health care services will benefit from the improvement of cultural sensitivity toward young children from multicultural families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Bu kapsamda çalışma, hemşirelik öğrencilerinin kültürler arası duyarlılık ve etnik merkezcilik düzeylerini ve etkileyen faktörleri belirlemek amacıyla yapıldı. (1,11,13,21,22,23,24), kültürel farklılıklara saygı (2,7,8,16,18,20), iletişimde kendine güvenme (3,4,5,6,10), iletişimden hoşlanma (9,12,15) ve iletişimde dikkatli olma (14,17,19)…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Bu kapsamda çalışma, hemşirelik öğrencilerinin kültürler arası duyarlılık ve etnik merkezcilik düzeylerini ve etkileyen faktörleri belirlemek amacıyla yapıldı. (1,11,13,21,22,23,24), kültürel farklılıklara saygı (2,7,8,16,18,20), iletişimde kendine güvenme (3,4,5,6,10), iletişimden hoşlanma (9,12,15) ve iletişimde dikkatli olma (14,17,19)…”
Section: Introductionunclassified
“…Kore'de okul hemşireleri ile yaptıkları çalışmada hemşirelerin kültürel duyarlılık puan ortalamalarını düşük olarak bulmuşlardır. Okul hemşirelerinin kültürler arası duyarlılıklarının geliştirilmesinin çok kültürlü aile yapılarına sahip çocukların sağlık hizmetlerinden daha etkin yararlanmasına yardımcı olacağı belirtilmişlerdir(20). Repo ve ark.…”
unclassified
“…Litina et al proves that understanding culture is important for the formation of one's wisdom [12]. Psychological education [13], nursing education [14], even medical education must also have a sensitivity to this cultural value [15]. For students the sensitivity and emotional intelligence to the noble values of this culture is very important for their daily life, such as for communication with teachers, to deal with collectivism conflict between friends [16], and to smooth students' involvement in academic activities.…”
Section: Analysis Of Results Of Teaching Materials Implementation Agaimentioning
confidence: 99%
“…For this reason, it is important for the teacher candidates to develop positive attitudes in order to create multicultural-friendly classrooms. Research studies investigating the two constructs revealed that there is a positive correlation between multicultural attitude and efficacy ( Bangura, 2018 ; Kim & Jang, 2012 ; Sela-Shayovitz & Finkelstein, 2020 ; Strickland, 2018 ; Suk et al, 2015 ; Yıldırım & Tezci, 2016 ). On the other hand, the studies mainly focused on a range of variables including gender, grade level, settlement and age.…”
Section: Introductionmentioning
confidence: 99%